“Degradação urbana e social: uma pesquisa longitudinal sobre vizinhança desequipada, habitação precária e alteridade no bairro da Liberdade em São Paulo” - Cunha, Moisés de Freitas (2021)
This research aims to analyze processes of degradation vis-à-vis processes of “revitalization” 7 in modern cities. For such proposes, São Paulo city, Liberdade district were selected, starting from the 19th century, in order to test the theory of racial transition of neighborhoods (GOTHAM), having as backbone the concept of social production of space (SANTOS) together the historic approach of São Paulo. Besides, there´s also a political approach by means of the Biopolitics concept, as per Foucault, plus some philosophers of the Politics known as contratualists. It aims to understand how rulers of modern cities, the Sovereigns, elaborate contracts with their subjects/city dwellers so that only a few of such groups and their neighborhoods are reached by public and/or private policies, this way either producing physical and/or symbolic degradation or revitalization or even gentrification. In short, who has got the power to make live and let die, or even make revitalize/gentrify and let degrade? For study cases, a few neighborhoods in the Liberdade district, Sao Paulo city have been selected, and the Brooklyn borough in New York, in the USA, where there has been the identification of zones subjected to degradation followed by revitalization, and later degradation again, in order to analyze the alternation of the situation of degradation and revitalization along more than one century, coinciding with the phenomenon “invasion-succession”, later re-baptized “theory of racial transition of neighborhoods” as per the US sociological approach known as Symbolic Interactionism. The main objective of this comparative study item is to emphasize the amplitude and depth of the relationship between Brazil and the United States of America, focusing the production of a set of ideas, guide-book that can prevent and/or correct processes of physical and/or symbolic degradation, analyzed in detail by means of the approach “social production of space” (SANTOS), resulted of biopolitics, and the historic liabilities produced by means of the enslavement of Africans and their descendants in Brazil and the United States, considering the wealth produced (wealth genealogy) that finances and/or promotes the European immigration, urbanization and industrialization of the studied areas